A sociocultural approach to effective listening skill development for Malaysian EFL students: A Literature Review - Islami, Annisa Permata; Saad, Mohd Rashid Bin Mohd (FKIP - Universitas Riau, 2024)
This literature review explores the development of effective listening skills among Malaysian English as a Foreign Language (EFL) students through a sociocultural lens. Recognizing the significance of sociocultural factors in language learning, this study examines various theories, strategies, and interventions pertinent to enhancing listening proficiency in this context. By synthesizing existing research, the review elucidates key socio-cultural influences on listening skill acquisition and offers insights into tailored pedagogical approaches to optimize listening skill development among Malaysian EFL learners. Thus, internationalization has become a desirable trend among learners to further their future study or professional world where English is the medium of instruction. As a result, Malaysian students look for strategies to help them overcome their academic comprehension challenges. This paper explores and better explains EFL Malaysian students’ academic listening challenges and strategies to motivate stakeholders to support in furthering their studies overseas or in the working world. Thus, this paper reviews related literature on academic listening strategies through the traditional literature review.